Assessing Heterosis for Grain Yield and Related Traits in Six-Row Barley (Hordeum vulgare L.) under Varying Sowing Conditions: Heterosis assessment in barley under varying sowing conditions - Kulheri, Anil; Rajput, S.S.; Punia, S.S.; Kiran Jakhar; Choudhary, Sunita (Journal of Cereal Research, 2025)
The present study was conducted to assess the magnitude of heterosis for grain yield and its component traits in six row barley (Hordeum vulgare L.) using a modified Triple Test Cross analysis with fifteen lines and three testers (RD 2508, RD 3005, and their F₁ hybrid RD 2508 × RD 3005). A total of 63 barley genotypes, including 15 lines, 3 testers, and 45 F₁ crosses, were evaluated during the 2022–23 Rabi season under three sowing environments (early, normal, and late) using a randomized block design with three replications. Pooled ANOVA showed significant genotypic differences across all traits studied. Across all environments, the crosses BG 105 × RD 2508, DWRUB 64 × RD 2508, PL 751 × RD 2508, RD 2035 × RD 2508, RD 2552 × RD 2508, BH 959 × RD 3005, HUB 113 × RD 3005, JB 110 × RD 3005, RD 2552 × RD 3005, RD 2907 × RD 3005, BG 105 × F₁, DWRUB 64 × F₁, DWRB 137 × F₁, RD 2035 × F₁, RD 2552 × F₁, and RD 2660 × F₁ exhibited significant heterobeltiosis for grain yield per plant in all three environments. These crosses can therefore be considered promising for enhancing barley yield under early, normal, and late sowing conditions.